2017
DOI: 10.3138/ptc.2016-47
|View full text |Cite
|
Sign up to set email alerts
|

Balance Assessment Practices of Saskatchewan Physiotherapists: A Brief Report of Survey Findings

Abstract: Purpose: This study was conducted to determine the balance assessment practices of physiotherapists in Saskatchewan. Methods: Practising physiotherapists who assess and treat adults with balance and mobility impairments were eligible to participate in this cross-sectional, online survey. The questions investigated the use of balance assessment measures, the balance components assessed, and practice area. Results: Of the 72 respondents, most reported regularly assessing five or more of the nine balance componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
(30 reference statements)
2
7
0
Order By: Relevance
“…With respect to fall prevention this is concerning as it is well-established that some of these under-targeted components, such as reactive balance, have an important and specific role in avoiding falls [32]. While there is little published data on community exercise program practices to compare against, these findings are consistent with related work in physical therapists that demonstrated that reactive balance is consistently under-assessed in Canada [33, 34]. Finally, a third important finding was the general absense of assessment in the programs discussed in this study.…”
Section: Discussionmentioning
confidence: 53%
“…With respect to fall prevention this is concerning as it is well-established that some of these under-targeted components, such as reactive balance, have an important and specific role in avoiding falls [32]. While there is little published data on community exercise program practices to compare against, these findings are consistent with related work in physical therapists that demonstrated that reactive balance is consistently under-assessed in Canada [33, 34]. Finally, a third important finding was the general absense of assessment in the programs discussed in this study.…”
Section: Discussionmentioning
confidence: 53%
“…Participants reported limitations of existing standardized tools for assessing reactive balance control, and consequently used informal observation of clients’ balance to inform treatment. Assessments such as the Berg Balance Scale and Timed Up and Go were often used by participants in our study, and are commonly used in other settings [29-31]. However, these tools do not include items related to reactive balance control, and it seems that participants were unaware of tools such as the Balance Evaluation Systems Test (BEST) [32] or the Performance Oriented Mobility Assessment (POMA) [33], which do include reactive balance control items.…”
Section: Discussionmentioning
confidence: 99%
“…Although reactive balance is impaired in numerous clinical populations [3][4][5][6], meta-analyses have determined that when it is improved through targeted exercise, it is associated with reduced number of falls and fallers [7,8]. And yet, in spite of this strong evidence, multiple studies have demonstrated that reactive balance is under-assessed by Canadian physiotherapists relative to other balance constructs (for example: anticipatory control, static, and dynamic stability) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%